Religious Organizations' Advocacy Strategies for Disability Rights: A Case Study of the Jaya Music Group of the Visually Impaired in Malioboro, Yogyakarta - Farid, Muhammad Rifa'at Adiakarti; Fawais, Moh; Amanda, Dhania Nurrizki; Azzahra, Annisya (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2024)
This study aims to analyze the advocacy strategies implemented by the Social Service Council of the Regional Leadership of Muhammadiyah in the Special Region of Yogyakarta (MPS PWM DIY) in addressing the case of Grup Jaya Musik, a group of blind musicians who faced obstacles in performing in the Malioboro area due to urban redevelopment policies. MPS PWM DIY, which has evolved into an organization with a broader scope of social services, plays a crucial role in advocating for the rights of people with disabilities. This research adopts a qualitative approach with a case study design. Data collection methods include observation, interviews, and documentation. The findings reveal that the advocacy strategy employed by MPS PWM DIY involves a multisectoral collaborative approach, realized through dialogues with stakeholders and cross-sector collaboration with local government and private sector entities. Additionally, MPS PWM DIY proactively advocates for legal certainty for the disabled community, emphasizing the urgency of inclusive and clear policy reforms. The study highlights the critical role of religious organizations in broader social advocacy and underscores the importance of a multisectoral collaborative approach in strengthening advocacy efforts. The findings from this study offer an advocacy model that can be adapted by other organizations in similar contexts and have significant implications for the development of disability rights advocacy strategies at the national level. Keywords: Advocacy Strategies, Disability Rights, Social Services, Multisectoral Collaboration   Penelitian ini bertujuan untuk menganalisis strategi advokasi yang diterapkan oleh Majelis Pelayanan Sosial Pimpinan Wilayah Muhammadiyah Daerah Istimewa Yogyakarta (MPS PWM DIY) dalam menangani kasus Grup Jaya Musik, sebuah kelompok musisi tunanetra yang mengalami hambatan untuk tampil di kawasan Malioboro akibat kebijakan penataan ulang. MPS PWM DIY, yang telah berkembang menjadi organisasi dengan cakupan pelayanan sosial yang lebih luas, memainkan peran krusial dalam memperjuangkan hak-hak penyandang disabilitas. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Metode pengumpulan data yang digunakan meliputi observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa strategi advokasi yang diterapkan oleh MPS PWM DIY melibatkan pendekatan kolaboratif multisektor, yang diwujudkan melalui audiensi dengan pemangku kepentingan serta kolaborasi lintas sektor dengan pemerintah daerah dan sektor swasta. Selain itu, MPS PWM DIY secara proaktif memperjuangkan kepastian hukum bagi kelompok difabel, dengan menekankan pada urgensi reformasi kebijakan yang inklusif dan jelas. Penelitian ini menyoroti pentingnya peran organisasi keagamaan dalam advokasi sosial yang lebih luas serta pentingnya pendekatan kolaboratif multisektor dalam memperkuat upaya advokasi. Temuan dari penelitian ini menawarkan model advokasi yang dapat diadaptasi oleh organisasi lain dalam konteks serupa dan memiliki implikasi yang signifikan bagi pengembangan strategi advokasi hak-hak penyandang disabilitas di tingkat nasional. Kata kunci: Strategi Advokasi, Hak Disabilitas, Layanan Sosial, Kolaborasi Multisektoral